Psychological and Social Factors in Jury Decision-Making: An Analysis of the Influence of Implicit Bias and Prejudice - João Miguel Alves Ferreira; Sergii Tukaiev (RevSALUS, 2025)
The decision of the jury in criminal trials is widely regarded as a cornerstone of democratic judicial systems, based on the premise that impartial individuals can objectively judge a case. However, a growing body of research suggests that psychological and social factors, such as implicit bias and cultural prejudices, can significantly influence the jury's decision-making process, compromising impartiality and potentially leading to judicial errors [1][3][5]. OBJECTIVES: This narrative review examines the impact of these factors in the forensic context, aiming to identify the mechanisms through which implicit bias and various forms of prejudice can distort jurors' judgement. METHODS: We conducted searches across databases such as PsycINFO, PubMed, EMBASE, Web of Science, Cochrane, and CINAH, following APA 7 guidelines. By analysing these narratives, we identify emerging patterns and areas of consensus, reflecting the complexity of the field. As we conclude this narrative, we are reminded that knowledge is fluid, constantly evolving, and that our current understanding is just a stop on an endless journey. RESULTS: Implicit bias refers to automatic attitudes or stereotypes that operate unconsciously, influencing behaviour and decision-making without the individual being fully aware of the process. In the forensic context, evidence suggests that implicit bias can affect how jurors perceive the defendant, witnesses, and the evidence presented. For example, research indicates that individuals from racial or socioeconomic minorities tend to be judged more harshly compared to defendants from majority groups, regardless of the objective evidence in the case. This phenomenon raises concerns about the fairness of the judicial system and the need for strategies to mitigate these biases. In addition to implicit bias, explicit prejudice, that is, conscious and deliberate attitudes, also plays a relevant role in jury decision-making. Jurors may be influenced by racial, gender, and class-based prejudices, which can interfere with the evaluation of evidence and the credibility of witnesses. Studies reveal that, in cases of violent crimes, racial prejudice can amplify the severity of sentences, particularly in cases involving victims from majority groups. These prejudices not only affect jurors’ perceptions of the defendant but also shape group deliberation dynamics, where jurors with prejudiced views can influence other members of the jury. This review also explores the role of psychological and legal interventions aimed at minimising the impact of implicit bias and prejudice on jury decisions. Implicit bias training programmes and stricter guidelines for juror selection have been suggested as effective strategies to promote greater impartiality in trials. Moreover, the use of technology, such as trial simulations and decision-support tools, has been proposed to help neutralise the effects of psychological biases in the judicial process [1][2][3][4][5]. CONCLUSION: While the jury system aims to ensure justice and impartiality, it is vulnerable to psychological and social influences that may compromise the fairness of verdicts. Understanding the factors that contribute to implicit bias and prejudice in jury decision-making is crucial for developing effective interventions that ensure fairer and more equitable trials in the forensic context.